Community currencies and social inclusion: A critical evaluation - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2005)
The challenge to create sustainable communities is identified as a core priority in 'Securing The Future', the UK government's strategy for sustainable development. Tackling social exclusion and building neighbourhood engagement are seen as principal elements of that objective, and there is an urgent need for tools and initiatives to achieve these aims. Community currencies are a grassroots innovation which claim to meet those goals. They are initiatives which develop and utilise an alternative medium of exchange, to enable people to trade goods and services without using cash. This paper evaluates a particular type of community currency - a time bank where participants use time as a unit of money - as a tool to overcome social exclusion. An innovative evaluation tool is developed to identify observable impacts of participation in the time bank, according to three criteria of social inclusion: achieving economic, social and political citizenship. A multi-method case study of a single time bank implements this appraisal tool, using postal surveys and interviews and focus groups with participants, document analysis, site visits and interviews with key stakeholders. It finds that the time bank is largely successful in meeting its social inclusion goals, and that the activity taking place is small in scale but very significant to the - mainly socially excluded - participants. A combination of government support to remove inhibitive social security regulations, and secure funding could enable time banking to grow into a powerful tool for building sustainable communities.
Keywords: 330; community currencies; social exclusion; Sustainable Communities; Sustainable Development; time banks